Analisis Spasio-Temporal Perubahan Luas Lahan Garam di Pesisir Kabupaten Rembang - Edwin Maulana; Guridno Bintar Saputro; Suprajaka Suprajaka; Cahyawati Mandala Sari (Department of Urban and Regional Planning, Diponegoro University, 2020)
The increase in salt consumption is not proportional to the growth of salt production land. So far, the mapping of salt ponds has been carried out on a small to medium scale, so the accuracy is not too good. This study aimed to analyze changes in large-scale salt ponds in Rembang Regency during the period of 2005-2015. The data source used is a Very High-Resolution Satellite Image (CSRST) which has been corrected and other secondary data. Salt area was calculated through visual interpretation and manual detection. CSRST data usage by visual interpretation methods and manual detection had advantages in terms of geometric accuracy compared with the use of medium-sized image of automation methods. The analysis showed that the area of salt land in Rembang Regency increased during 2005-2015. The biggest increase occurred in 2005-2011, which increased by 546,255 ha or by 32%. The increase in area during 2011-2015 was not significant by 198.45 ha (11.46%). Area expansion was expected to occur in the next few years, but it was not expected to be significant because of the optimal land use in the most of Rembang already. Expansion of salt ponds remained possible by converting the existing rice fields on the coast of Rembang Regency. However, a comparative study of the economic value of rice fields and salt ponds must be carried out before converting the paddy fields to salt ponds.